HCWM System: a software to support medical waste disposal (Research, Society and Development, 2023)
Waste management is a challenge for healthcare institutions. Several factors influence the proper handling of these residues, from segregation to final disposal. The objective of this work was to develop a software to support management of medical waste disposal at “Hospital Universitário de Maringá” (HUM) – a teaching hospital supported by “Universidade Estadual de Maringá”. This is a descriptive and retrospective study through data collection to determine the amount of waste generated at HUM, according to classification and estimated expenses related to final disposal. A survey of requirements for the construction of the software was also carried out by verifying the needs for its development and implementation. The results showed the amount of waste generated by sector, according to classification, and the calculated value for waste disposal. The study enabled the development of a software to support management and aid in various stages of managing HUM's medical waste.